Tourism 4.0: Strategi komunikasi pemasaran pariwisata kota semarang (Faculty of Communications Science, Dr. Soetomo University, 2020)
The city of Semarang was ranked the 4th best tourism city in Indonesia in the 2018’s Yokatta Wonderful Indonesia Tourism Award. The number of tourists visiting the city has seen a significant increase from 2.09 million visitors in 2011 to around 5,02 million by 2017. This development also can not be separated from the marketing strategy adopted by Government of the City of Semarang which currently has also developed the Semarang Smart City Program. That is, the role of technology, in this case digital media, becomes a reference that will be used to be able to access all information, especially on tourism, or known as the tourism 4.0. The theory used in this research is Marketing Public Relations by Thomas El Harris. This study aims to find out how the marketing strategy implemented by the Semarang City Government in conducting tourism promotion through digital media. Researchers used descriptive qualitative research methods with in-depth interviews and observations. The results showed that Government has various platforms to promote tourism, namely WisSemar and My Semarang Travel Guide for smartphone application, Facebook, Instagram, Twitter and Youtube. The aim is that people come and visit Semarang both to attend events and visit tourist attractions. Pull strategy is used by Disbudpar to attract the attention of the public by uploading information about all events held in Semarang through social media.Keywords: Tourism 4.0; Tourism; Tourism Promotion; Marketing; Semarang.